A ritualistic reading of Mark 7:1–23 - Hombana, Mphumezi (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2024)
This article examines the ritual dynamics and identity negotiation in Mark 7:1–23, aiming to unpack the complex interaction between ritual practices and social identity in early Christian communities. Drawing on ritual theory from anthropology and sociology, this research analyses the significance of ritual purity and its implications for group identity formation and maintenance. Mark 7:1–23 presents a confrontation between Jesus and the Pharisees about the observance of the handwashing ritual before meals, highlighting opposing understandings of purity and religious tradition between Jesus and the Pharisees. Jesus’s critique of an external ritual of handwashing as an identity marker emphasises the purity of the heart as a valid identity marker for all children of God. Through a ritualistic reading of Mark 7:1–23, this article seeks to explore the role played by rituals in identity formation in antiquity. By engaging with ritual theory as a lens to unpack the Pharisees’ perspective and that of Jesus on what identifies a true child of God, this article aims to offer insights into the complexities of identity as understood by both Jesus’s early movement and the Pharisees.Contribution: This interdisciplinary study of Mark 7:1–23 utilises ritual theory to expose the interaction between ritual practices and identity negotiation within early Christian communities, revealing how Jesus’s critique of external rituals facilitated the formation of a distinctively Christian identity centred on inner transformation and ethical conduct.